Casein Kinase 2α Ablation Confers Protection Against Metabolic Dysfunction‐Associated Steatotic Liver Disease: Role of FUN14 Domain Containing 1‐Dependent Regulation of Mitophagy and Ferroptosis - Ke He; Meixiao Zhan; Xuanming Luo; Ruibing Li; Ling Lin; Jie Lin; Liheng Li; Hongdong Chen; Gary D. Lopaschuk; Hao Zhou; Fei Liu; Jun Ren (MedComm, 2025)
ABSTRACT Mitochondrial dyshomeostasis provokes the onset of metabolic dysfunction‐associated steatotic liver disease (MASLD) although its precise involvement in particular mitophagy in MASLD remains elusive. This work evaluated the role of casein kinase 2α (CK2α) and FUNDC1 in high‐fat diet (HFD)‐evoked MASLD. WT and CK2α deletion (CK2α‐/‐) mice were subjected to low fat or HFD for 20 weeks. Global metabolism, AST, ALT, cholesterol, triglycerides, hepatic steatosis, fibrosis, inflammation, mitochondrial injury, mitophagy and ferroptosis were examined. Bioinformatics analysis enriched mitochondria‐related pathways in MASLD. Hepatic CK2α and FUNDC1 were upregulated and downregulated, respectively, in MASLD patients and HFD‐fed mice. HFD led to adiposity, hepatomegaly, hepatic steatosis, fibrosis, inflammation, ferroptosis, mitochondrial injury, elevated hepatic tissue Fe2+, FAS, CHREBP, SREBP1, PGC1α, PPARα, PPARγ, SCD1, PEPCK, G6Pase, and DGAT1 as well as downregulated FUNDC1, GPx4, SLC7A11 and NCOA4, the effects (except for NCOA4) were nullified by CK2α deletion. FUNDC1 deletion nullified CK2α deletion‐evoked benefit on hepatic ferroptosis and lipid enzymes. In vitro study using palmitic acid indicated an obligatory role for CK2α, FUNDC1 and ferroptosis in hepatocyte steatosis. Collectively, our results demonstrated that CK2α activation by HFD serves as a trigger for mitochondrial damage, hepatic injury, and pathogenesis of MASLD through FUNDC1 disruption and ferroptosis.